Роль VPN у забезпеченні безпеки в інтернеті - Канарик, А. В. (ХНУРЕ, 2023)
This report emphasizes the significance of safeguarding sensitive information transmitted over the internet, especially in the face of growing computer usage and internet accessibility, which has resulted in more sophisticated security risks. To combat hackers and ensure the security of devices and data, the use of a Virtual Private Network (VPN) is an effective solution.
Keywords: безпека в інтернеті